2005
DOI: 10.1055/s-2005-837665
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Insulin Action in Polycystic Ovary Syndrome

Abstract: We found a higher prevalence of the T45 G polymorphism in the adiponectin gene in women with PCOS compared to controls. This was not associated with a more insulin resistant phenotype in PCOS, however. Other frequent polymorphisms in genes related to insulin resistance and type 2 diabetes showed no association with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 27 publications
1
49
2
1
Order By: Relevance
“…Whereas most studies (9)(10)(11)(12)14,15), present study included, reported no association between Pro12Ala genotype and PCOS diagnosis, a few reported that the Pro12Ala G allele was significantly less frequent in PCOS versus control women (13,16). Additionally, some studies reported significant increases in insulin sensitivity (decreased HOMA-IR) and decreases in fasting insulin and glucose levels (8-10) and lower hirsutism score (9) in PCOS women with the Pro12Ala G allele; whereas others (7,11,14), including this study, reported no association with fasting glucose and insulin or changes in HOMA-IR in those with PCOS. Only a subset of the subjects in our study was phenotyped for insulin-related traits, which may explain why we did not observe association with these traits in subjects with PCOS; however, this subset was still greater in number than each of the reports that did find an effect of Pro12Ala on insulin-related traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most studies (9)(10)(11)(12)14,15), present study included, reported no association between Pro12Ala genotype and PCOS diagnosis, a few reported that the Pro12Ala G allele was significantly less frequent in PCOS versus control women (13,16). Additionally, some studies reported significant increases in insulin sensitivity (decreased HOMA-IR) and decreases in fasting insulin and glucose levels (8-10) and lower hirsutism score (9) in PCOS women with the Pro12Ala G allele; whereas others (7,11,14), including this study, reported no association with fasting glucose and insulin or changes in HOMA-IR in those with PCOS. Only a subset of the subjects in our study was phenotyped for insulin-related traits, which may explain why we did not observe association with these traits in subjects with PCOS; however, this subset was still greater in number than each of the reports that did find an effect of Pro12Ala on insulin-related traits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a polymorphism in exon 2 of the PPARγ2 isoform, resulting in a Pro12Ala substitution, influences the risk of type 2 diabetes with the rarer Ala allele associated with a lower incidence of diabetes (6). Several small studies have looked at the effects of the Pro12Ala and a silent exon 6 polymorphism (His447His) in association with PCOS, though they have produced conflicting results (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). To better understand the role of these polymorphisms in PCOS, we examined the Pro12Ala and silent exon 6 polymorphism in a cohort of 285 women with PCOS and 187 controls, the largest sample size of all published reports of PPARG in PCOS to date.…”
mentioning
confidence: 99%
“…After review, a total of 16 published articles reported on the relationship between these two IRS gene polymorphisms and PCOS met the inclusion criteria [12][13][14][15][19][20][21][22][23][24][25][26][27][28][29], 15/16 were about the Gly972Arg polymorphism, 5/16 were about the Gly1057Asp polymorphism. These articles were published between 2001 and 2011.…”
Section: Eligibility Of Studiesmentioning
confidence: 99%
“…51 A second single nucleotide polymorphism, T45G, has been investigated in relation to PCOS, and studies have shown a statistically definable Adipokines in reproduction DB Campos et al correlation between the occurrence of this gene form and the ovarian disorder. 52,53 Recent findings indicate that adiponectin may also be active in the uterus and placenta. Both AdipoR1 and R2 are highly expressed in the endometrium of the pig.…”
Section: Effects Of Adiponectin On Reproduction and Fertilitymentioning
confidence: 99%